PENGARUH PENGETAHUAN PERKOPERASIAN DAN MOTIVASI TERHADAP PERILAKU BERKOPERASI PADA KOPERASI HESTI WIRA SAKTI - Fatmawati yarso; F.Y. Khosmas; Okianna Okianna (Universitas Tanjungpura, 2019)
AbstractThis research aims to determine whether there is an influence of knowledge and motivation on cooperative behavior in the cooperative of Hesti Wira Sakti Kesdam XII/TPR. The method used in this research is an associative research method with a form of research to determine the relationship between two or more variables. The population in this research was 217 people. The sample used was a cooperative member of the army totaling 57 people. To the determine the sample of this research, the writer using proportionate stratified random sampling. The techniques of data collection consisted of indirect communication tecnique and documentary study technique. The tool of collecting data was questionnaire. The was calculated and the result showed that there was a significant influence between the independent variables (X1) and (X2) on the dependent variable Y. Based on the analysis, thecalculation of t-test data obtained sig. 0,018 < 0,05 (alpha 5%) which shows the influence of knowledge of cooperatives on cooperative behavior. Whereas, the variable t-test of cooperative motivation shows sig. 0,175 > 0,05 (Alpha 5%) which shows there is no influence between cooperative motivation on cooperative behavior. Whereas, the f-test carried out simultaneously shows sig. 0,000b< 0,05 (Alpha 5%) which means there is an influence between cooperative knowledge and motivation on cooperative behavior.Keywords:Knowledge, Motivation and Cooperative Behavior